Poplar / willow catkin-based flexible porous carbon tube loaded iron-zinc composite material as well as preparation method and application thereof

The preparation of the iron-zinc composite material of poplar/cattle-based flexible porous carbon tube loaded by carbon thermal reduction method solves the problem of difficulty in utilization of poplar/cattle-cattle fiber and the recycling of biomass carbon materials, and achieves efficient water pollution degradation and CO2 adsorption, and the material can Recycling avoids secondary pollution.

CN119303585APending Publication Date: 2025-01-14WUHAN POLYTECHNIC UNIVERSITY
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411251229.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-07
Publication Date
2025-01-14

AI Technical Summary

Technical Problem

The prior art is difficult to effectively utilize poplar/cattle fiber, and the particles of biomass carbon materials are small and difficult to recycle after carbonization, resulting in secondary pollution and waste of resources, and lack of efficient CO2 adsorbents and water pollution degradation catalysts.

Method used

The carbon-thermal reduction method was used to prepare the iron-zinc composite material of the poplar/cats-based flexible porous carbon tube. The poplar/cats were treated by the ethanol solvent-thermal method, and the iron-zinc-loaded photofenton catalyst was calcined under a nitrogen atmosphere. Its porous structure and iron-zinc doping improve catalytic and adsorption properties.

Benefits of technology

It achieves efficient degradation of water pollutants and good adsorption of CO2, and the catalyst remains efficient in multiple cycles. The material is flexible and magnetic, which is easy to recycle and utilize and avoids secondary pollution.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119303585A_ABST
    Figure CN119303585A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of water pollution treatment catalysts, and discloses a poplar / willow catkin-based flexible porous carbon tube loaded iron-zinc composite material as well as a preparation method and application thereof. The preparation method comprises the following steps: crushing, cleaning and drying poplar / willow catkin to obtain pure poplar / willow catkin, pretreating the pure poplar / willow catkin through an ethanol solvothermal method to obtain lignin-removed poplar / willow catkin, dissolving ferric iron salt and divalent zinc salt in a solvent, and stirring to obtain a mixed solution; putting the lignin poplar / willow catkins into the mixed solution, stirring, and adjusting the pH to be alkaline to obtain a turbid liquid; stirring and filtering the turbid liquid, adjusting the pH value to be neutral, carrying out suction filtration, and drying to obtain an iron and zinc loaded poplar / willow catkin tube; and pre-oxidizing and calcining to obtain the poplar / willow catkin-based flexible porous carbon tube loaded iron-zinc composite material. The poplar / willow catkin-based flexible porous carbon tube loaded iron-zinc composite material is easy to separate and recover, can be used as a photo-Fenton catalyst in water pollution degradation, and has excellent water system pollution degradation capability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of catalysts for treating water pollution, and in particular to a poplar / willow catkin-based flexible porous carbon tube-loaded iron-zinc composite material, and a preparation method and application thereof. Background Art

[0002] In recent years, due to the serious problem of water pollution, advanced oxidation technology is often used to degrade pollutants in water bodies. Photo-Fenton technology has been widely studied because of its mild reaction conditions, simple equipment and wide application range. Photo-Fenton technology can better reduce the cost of wastewater treatment and improve treatment efficiency. The performance of degrading organic pollutants mainly depends on the photocatalytic activity of the photocatalyst. Iron-based photocatalysts with visible light response have greater potential in the photo-Fenton reaction. Iron-based visible light catalysts can generate electrons and holes under visible light, and the photogenerated electrons may reduce Fe 3+ Fe 2+ , promoting Fe 2+ It reacts with H2O2 to continuously produce ·OH; it may also directly reduce H2O2 to produce ·OH, thereby purifying the water.

[0003] With the rapid development of industrial processes, greenhouse gas emissions have increased year by year, exacerbating the greenhouse effect. In order to alleviate the intensification of the greenhouse effect, it is urgent to research and develop an efficient adsorbent for adsorbing CO2 in the environment. First of all, reduce the emission of CO2 from the source. The capture, storage and utilization technology of CO2 is an effective way to solve greenhouse gas emissions. Biomass carbon comes from the environment and is a low-cost carbon-based material. Its rich functional groups on the surface and sufficient pore structure make it a good adsorbent. Poplar / willow trees are widely distributed in my country due to their excellent greening properties. They are planted on a large scale for economic timber, shelterbelts, water and soil conservation and environmental greening. The poplar / willow catkin fibers produced by poplar / willow trees are short in length, small in diameter, and weak in tensile strength. They are generally not used for spinning, and their other utilization values ​​are not high and difficult to use. They usually appear as agricultural waste. However, poplar / willow catkin fibers are natural fibers with a high cellulose content. They are derived from biomass and contain a large number of hydroxyl groups on their surface. The hydroxyl groups on the molecular chains of poplar / willow catkin fibers are functionalized and used as a biomass carbon material in the field of adsorption. In addition, since the particles of biomass carbon materials are small after carbonization, they are difficult to recycle and are not conducive to reuse, resulting in secondary pollution.

[0004] Therefore, the present invention proposes a poplar / willow catkin-based flexible porous carbon tube-loaded iron-zinc composite material prepared by a carbothermal reduction method to solve the above problems. Summary of the invention

[0005] Based on the above, the purpose of the present invention is to provide a poplar / willow catkin-based flexible porous carbon tube-loaded iron-zinc composite material and its preparation method and application, which has excellent adsorption performance and is used in degrading water system pollution.

[0006] A method for preparing a poplar / willow catkin-based flexible porous carbon tube-loaded iron-zinc composite material comprises the following steps:

[0007] The poplar / willow catkins are crushed, cleaned and dried to obtain pure poplar / willow catkins; the pure poplar / willow catkins are pretreated by an ethanol solvothermal method to obtain delignified poplar / willow catkins;

[0008] Dissolving a trivalent iron salt and a divalent zinc salt in a solvent, stirring, and obtaining a mixed solution;

[0009] Adding deligninized poplar / willow catkins into the mixed solution and stirring, adjusting the pH to alkaline, and obtaining a suspension;

[0010] The suspension is stirred, filtered, the pH is adjusted to be neutral, filtered, and dried to obtain a poplar / willow catkin tube loaded with iron and zinc;

[0011] The poplar / willow catkin tube loaded with iron and zinc is pre-oxidized and calcined to obtain a poplar / willow catkin-based flexible porous carbon tube loaded with iron and zinc composite material.

[0012] As a preferred embodiment of the preparation method of a poplar / willow catkin-based flexible porous carbon tube-loaded iron-zinc composite material, in the mixed solution, the concentration of the divalent zinc salt is 10 mmol / L-30 mmol / L, and the mass ratio of the trivalent iron salt to the divalent zinc salt is 1:2; in the suspension, the concentration of the delignified poplar / willow catkins is 8-12 g / L.

[0013] As a preferred embodiment of the preparation method of a poplar / willow catkin-based flexible porous carbon tube-loaded iron-zinc composite material, the trivalent iron salt includes one or more of ferric nitrate, ferric sulfate, and ferric acetylacetonate, the divalent zinc salt includes one or more of zinc nitrate, zinc chloride, and zinc acetate, and the solvent includes anhydrous ethanol; when the divalent zinc salt and the trivalent iron salt are dissolved in the solvent, the stirring time is 10-60 minutes.

[0014] As a preferred scheme for the preparation method of a poplar / willow catkin-based flexible porous carbon tube-loaded iron-zinc composite material, when the pure poplar / willow catkins are pretreated by an ethanol solvothermal method, the specific process includes: adding pure poplar / willow catkins and ethanol into a reaction kettle, sealing and placing in an oven for reaction, taking out and filtering to obtain pretreated poplar / willow catkins and lignin black liquor, washing the pretreated poplar / willow catkins with anhydrous ethanol, washing until the filtrate is clear, and obtaining delignified poplar / willow catkins.

[0015] As a preferred embodiment of the preparation method of a poplar / willow catkin-based flexible porous carbon tube-loaded iron-zinc composite material, the liquid-to-solid ratio of the ethanol to the pure poplar / willow catkins is (15-120):1, and the concentration of the ethanol is 40-80%; during the sealed heating reaction, the reaction temperature is 150-230°C and the reaction time is 0.5-3.5h.

[0016] As a preferred solution for the preparation of a poplar / willow catkin-based flexible porous carbon tube-loaded iron-zinc composite material, the pH is adjusted to alkaline, with a pH value of 9-10.

[0017] As a preferred scheme for the preparation method of a poplar / willow catkin-based flexible porous carbon tube-loaded iron-zinc composite material, during the pre-oxidation process, the temperature is increased to 250-300°C at a rate of 0.5-2°C / min and kept warm for 30-90min; during the calcination temperature process, the temperature is increased to 700-800°C at a rate of 3-6°C / min and kept warm for 30-90min, and an inert atmosphere is maintained during the calcination process.

[0018] A poplar / willow catkin-based flexible porous carbon tube-loaded iron-zinc composite material is prepared by any one of the preparation methods described above.

[0019] A photo-Fenton catalyst comprises a poplar / willow catkin-based flexible porous carbon tube-loaded iron-zinc composite material.

[0020] A catalytic method for a photo-Fenton catalyst performs photo-Fenton degradation under the conditions of different synthesis systems with different iron-zinc doping amounts, alcohol phase or water phase.

[0021] The beneficial effects of the present invention are:

[0022] The invention provides a poplar / willow catkin-based flexible porous carbon tube-loaded iron-zinc composite material and a preparation method and application thereof. Delignified poplar / willow catkins are used as carbon sources, Fe salts and Zn salts are used as raw materials, and a photo-Fenton catalyst loaded with iron and zinc is prepared by a carbon thermal reduction method. When the poplar / willow catkins fiber is modified by iron salt, zinc salt and NaOH together, the zinc and iron addition amount is 1mmol:2mmol, and the pH is 9, the poplar / willow catkin-based flexible porous carbon tube-loaded iron-zinc composite material catalyst obtained by calcining in a nitrogen atmosphere has the highest catalytic efficiency, and the degradation rate of 50ml 300mg / L RhB in 1min reaches more than 99%. In addition, it has good catalytic performance for other dyes such as MB and MO, and 300mg / L of dyes can be basically degraded completely in 2min.

[0023] The poplar / willow catkins-based flexible porous carbon tube-loaded iron-zinc composite material has good recycling performance. The poplar / willow catkins-based flexible porous carbon tube-loaded iron-zinc composite material is not easy to break into powder due to its flexibility, and has a porous tubular morphology that is convenient for separation, recovery and recycling from water. After four cycles, it still has a high adsorption capacity for the dye Rhodamine B, and the degradation rate can still reach 99% or more after four adsorptions. In addition, the poplar / willow catkins porous carbon has good adsorption performance for CO2. Under the conditions of 273K and 101kPa, its CO2 adsorption capacity is 0.93mmol / g, and when zinc salt is introduced, its adsorption capacity is greatly improved to 1.71mmol / g. Therefore, the poplar / willow catkins-based flexible porous carbon tube-loaded iron-zinc composite material can also be used in gas adsorption.

[0024] Since the particles of poplar / willow catkins are small after carbonization and difficult to recycle, the preparation method of the present application loads iron-based materials during the preparation process to obtain magnetic carbon materials. This is not only beneficial to the recovery of biochar materials and their reuse to avoid secondary pollution, but also the loaded iron-based substances can be used to react and combined with adsorption to accelerate the treatment of pollutants in water bodies. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] In order to more clearly illustrate the technical solutions in the embodiments of the present invention, the following briefly introduces the drawings required for use in the description of the embodiments of the present invention. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the contents of the embodiments of the present invention and these drawings without paying any creative work.

[0026] Figure 1 IR spectra of poplar / willow catkin-based flexible porous carbon nanotubes loaded with different zinc and iron doping amounts, where (a) is PC-1, (b) is PC-Zn, (c) is PC-Fe, (d) is PC-Zn / Fe-2, and (e) is PC-Zn / Fe-4;

[0027] Figure 2 The XRD patterns of poplar / willow catkin-based flexible porous carbon nanotubes loaded with different zinc and iron doping amounts, where (a) is PC-Fe, (b) is PC-Zn, (c) is PC-Zn / Fe-1, (d) is PC-Zn / Fe-2, (e) is PC-Zn / Fe-3, and (f) is PC-Zn / Fe-4;

[0028] Figure 3 These are SEM images of poplar / willow catkin porous carbon and poplar / willow catkin-based flexible porous carbon tubes loaded with iron-zinc composites, where (a, b, c) are PC-1 and (d, e, f) are PC-Zn / Fe-2;

[0029] Figure 4It is the mapping image and EDS spectrum of PC-Zn / Fe-2 composite material;

[0030] Figure 5 The Raman spectra of poplar / willow catkin-based flexible porous carbon tubes loaded with different zinc and iron doping amounts of iron-zinc composite materials, where (a) is PC-1, (b) is PC-Zn, (c) is PC-Fe, and (d) is PC-Zn / Fe-2;

[0031] Figure 6 It is the N2 adsorption-desorption curve and pore size distribution diagram of poplar / willow catkin-based flexible porous carbon tubes loaded with different zinc and iron doping amounts of iron-zinc composite materials;

[0032] Figure 7 This is a graph showing the CO2 adsorption performance of different composite materials;

[0033] Figure 8 The photo-Fenton degradation curve and kinetic curve of RhB by poplar / willow catkin flexible porous carbon tubes loaded with different zinc and iron doping amounts and iron-zinc composite materials;

[0034] Fig. 9 This is the degradation effect diagram of PC-Zn / Fe-2 composite material on different dye wastewater;

[0035] Fig.10 The three-dimensional fluorescence spectra of PC-Zn / Fe-2 degrading RhB, where (a) is before adsorption, (b) is after adsorption, and (c) is after reaction;

[0036] Fig.11 is the performance diagram of PC-Zn / Fe-2 photo-Fenton cycle;

[0037] Fig.12 is the effect of different free radical scavengers on the photo-Fenton degradation of RhB by PC-Zn / Fe-2;

[0038] Fig.13 This is the magnetic properties test diagram of PC-Zn / Fe-2;

[0039] Fig.14 This is a flexibility test diagram of poplar fluff-based flexible porous carbon tube-loaded iron-zinc composite material. DETAILED DESCRIPTION

[0040] For ease of understanding of the present invention, the present invention will be described more fully below. The present invention can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the understanding of the disclosure of the present invention more thorough and comprehensive. Unless otherwise defined, all technical and scientific terms used in the present invention belong to the technical field of the present invention.

[0041] This embodiment provides a poplar / willow catkin-based flexible porous carbon tube-loaded iron-zinc composite material, comprising the following steps:

[0042] S100: crushing, washing and drying poplar / willow fluff to obtain pure poplar / willow fluff;

[0043] Specifically, the poplar / willow catkins are cleaned with deionized water, and dried at 50-70°C. The drying temperature can be set to 50°C, 60°C or 70°C, preferably 60°C, which is determined according to actual conditions.

[0044] S200: pure poplar / willow catkins were pretreated by ethanol solvothermal method to obtain delignified poplar / willow catkins;

[0045] Specifically, the specific process of pretreating pure poplar / willow catkins by ethanol solvent thermal method includes: adding pure poplar / willow catkins and ethanol into a reactor, sealing and heating the reaction, taking out and filtering to obtain pretreated poplar / willow catkins and lignin black liquor, washing the pretreated poplar / willow catkins with anhydrous ethanol, washing until the filtrate is clear, and obtaining delignified poplar / willow catkins.

[0046] More specifically, the liquid-solid ratio of ethanol to pure poplar / willow catkins is (15-120):1, the concentration of ethanol is 40-80%, the liquid-solid ratio of ethanol to pure poplar / willow catkins can be set to 120:1, 60:1, 40:1, 30:1, 24:1, 20:1, 17:1 or 15:1, and the ethanol concentration can be set to 40% or 50% or 80%; during the sealed heating reaction, the reaction temperature is 150-230°C, and the reaction time is 0.5-3.5h. The reaction temperature can be set to 150°C or 190°C or 230°C, and the reaction time can be set to 0.5h or 2h or 3.5h, which is determined according to the actual situation.

[0047] S300: dissolving a trivalent iron salt and a divalent zinc salt in a solvent, stirring, and obtaining a mixed solution;

[0048] Specifically, in the mixed solution, the concentration of divalent zinc salt is 10mmol / L-30mmol / L, which can be set to 10mmol / L or 20mmol / L or 30mmol / L, depending on the actual situation. The mass ratio of trivalent iron salt to divalent zinc salt is 1:2. In the suspension, the concentration of delignified poplar / willow catkins is 8-12g / L, which can be set to 8g / L or 10g / L or 12g / L, depending on the actual situation.

[0049] More specifically, the ferric iron salt includes one or more of ferric nitrate, ferric sulfate, and ferric acetylacetonate, the divalent zinc salt includes one or more of zinc nitrate, zinc chloride, and zinc acetate, and the solvent includes anhydrous ethanol; when the divalent zinc salt and the ferric iron salt are dissolved in the solvent, the stirring time is 10-60 minutes. The stirring time can be set to 10 minutes, 30 minutes, or 60 minutes, which is determined according to the actual situation.

[0050] S400: adding lignin poplar / willow catkins into the mixed solution and stirring, adjusting the pH to alkaline, and obtaining a suspension;

[0051] Specifically, the pH is adjusted to alkaline, with a pH value of 9-10.

[0052] S500: stirring the suspension, filtering, adjusting the pH to neutral, suction filtering, and drying to obtain poplar / willow catkin tubes loaded with iron and zinc;

[0053] S600: pre-oxidizing and calcining the poplar / willow catkin tube loaded with iron and zinc to obtain a poplar / willow catkin-based flexible porous carbon tube loaded with iron and zinc composite material.

[0054] Specifically, during the pre-oxidation process, the temperature is increased to 250-300°C at a rate of 0.5-2°C / min and kept warm for 30-90min. It can be set to increase the temperature to 300°C at a rate of 0.5°C / min and keep warm for 90min, or increase the temperature to 250°C at a rate of 2°C / min and keep warm for 30min, or increase the temperature to 270°C at a rate of 1°C / min and keep warm for 60min. During the calcination temperature process, the temperature is increased to 700-800°C at a rate of 3-6°C / min and kept warm for 30-90min. It can be set to increase the temperature to 700°C at a rate of 3°C / min and keep warm for 30min, or increase the temperature to 800°C at a rate of 6°C / min and keep warm for 90min, or increase the temperature to 750°C at a rate of 5°C / min and keep warm for 60min. An inert atmosphere is maintained during the calcination process, which is determined according to actual conditions.

[0055] The present invention will be further described below by means of specific examples.

[0056] Example 1

[0057] The poplar fluff was crushed, cleaned with deionized water, and dried at 60° C. to obtain clean poplar fluff.

[0058] Take 3.5g poplar fluff and 60mL 70% ethanol and add them to the reactor, quickly seal it, pre-treat it, place it in a 200℃ oven, take it out after reacting for 2h, and filter it to obtain the pre-treated poplar fluff fiber and lignin black liquor. Wash the pre-treated poplar fluff with anhydrous ethanol and wash until the filtrate is clear. Obtain the dried and washed lignin poplar fluff;

[0059] Weigh 1mmol of zinc nitrate and 2mmol of ferric nitrate into a conical flask, add 50mL of anhydrous ethanol, stir evenly, add 0.5g of delignified poplar fluff, stir evenly, add 6mol / L sodium hydroxide to adjust pH = 9-10, obtain a brown suspension, stir for 30min, and filter. Wash with alcohol until the pH is neutral, filter, and dry. Place the poplar fiber in a porcelain boat, pre-oxidize in a muffle furnace, heat to 270℃ at a rate of 1℃ / min, and keep warm for 60min. Transfer the porcelain boat cooled to room temperature to a tubular furnace, heat to 750℃ at a rate of 5℃ / min, and keep warm for 60min. Finally, a poplar-based flexible porous carbon tube-loaded iron-zinc composite material is obtained, named PC-Zn / Fe-2 (where PC is delignified poplar porous carbon).

[0060] Example 2

[0061] The preparation process and reaction conditions were consistent with those in Example 1, wherein Zn(NO3)2 was 0.5 mmol, Fe(NO3)3 was 1 mmol, and NaOH was added for reaction to obtain a poplar-based flexible porous carbon tube-loaded iron-zinc composite material, named PC-Zn / Fe-1.

[0062] Example 3

[0063] The preparation process and reaction conditions were consistent with those in Example 1, wherein Zn(NO3)2 was 1.5 mmol, Fe(NO3)3 was 3 mmol, and NaOH was added for reaction to obtain a poplar-based flexible porous carbon tube-loaded iron-zinc composite material, named PC-Zn / Fe-3.

[0064] Example 4

[0065] The preparation process and reaction conditions were consistent with those of Example 1, wherein 3.5 g of catkins were reacted with 60 mL of 70% ethanol, wherein Zn(NO3)2 was 1 mmol and Fe(NO3)3 was 2 mmol, and NaOH was added to react to obtain a catkin-based flexible porous carbon tube-loaded iron-zinc composite material, named PC-Zn / Fe-5.

[0066] In order to further illustrate the excellence of the present application, comparative examples 1-6 are added for illustration.

[0067] Comparative Example 1

[0068] The preparation process and reaction conditions were consistent with those of Example 1, wherein Zn(NO3)2 was 1 mmol, Fe(NO3)3 was 2 mmol, and NaOH was not added for the reaction to obtain a poplar-based flexible porous carbon tube-loaded iron-zinc composite material, named PC-Zn / Fe-4.

[0069] Comparative Example 2

[0070] The preparation process and reaction conditions were consistent with those of Example 1, wherein Zn(NO3)2 was 0 mmol, Fe(NO3)3 was 2 mmol, and NaOH was added for reaction to obtain a composite material of poplar-based flexible porous carbon tubes loaded with iron, named PC-Fe.

[0071] Comparative Example 3

[0072] The preparation process and reaction conditions were consistent with those of Example 1, wherein Zn(NO3)2 was 1 mmol, Fe(NO3)3 was 0 mmol, and NaOH was added for reaction to obtain a composite material of poplar-based flexible porous carbon tubes loaded with zinc, named PC-Zn.

[0073] Comparative Example 4

[0074] Consistent with the preparation process and reaction conditions of Example 1, the delignified poplar fluff was replaced with original poplar fluff carbon, wherein Zn(NO3)2 was 1 mmol and Fe(NO3)3 was 2 mmol, and NaOH was added for reaction to obtain zinc-loaded poplar fluff carbon tubes, named C-Zn / Fe (where C is original poplar fluff carbon).

[0075] Comparative Example 5

[0076] The preparation process and reaction conditions were consistent with those of Example 1, wherein Zn(NO3)2 was 0 mmol, Fe(NO3)3 was 0 mmol, and NaOH was added for reaction to obtain porous carbon tubes, named PC-1.

[0077] The specific formulas of various embodiments and comparative examples are shown in Table 1.

[0078] Table 1 Preparation formula of poplar-based flexible porous carbon tubes prepared with different zinc and iron doping amounts

[0079]

[0080] The poplar / willow catkin porous carbon tube-loaded iron-zinc composite materials prepared in the above examples and comparative examples were observed for morphology using characterization instruments and analyzed for performance.

[0081] 1. IR analysis

[0082] IR was measured by Fourier transform infrared spectrometer. The measurement range was 4000~500cm -1 , pressed with KBr. IR can identify the organic functional groups on the surface of porous carbon materials to analyze the composition of carbon materials.

[0083] like Figure 1 As shown in the figure, after high temperature carbonization, the delignified poplar fluff porous carbon has a wavelength of 3420 cm -1 The nearby -OH stretching vibration peak is significantly weakened. Figure 1(b) Zinc salt was introduced into the carbon tube. As shown in the figure, the -1 Obvious CH, C=C, and CH characteristic absorption peaks can be seen. Figure 1 (c) It can be seen that due to the addition of iron salt, the -1 A new strong absorption peak appears at , which corresponds to the C=C double bond stretching vibration peak, which means that the addition of iron salt increases the carbonization degree of carbon materials. Figure 1 (d) It can be seen that due to the addition of zinc salt and iron salt, the -1 A new strong absorption peak appeared at 620 cm-1, corresponding to the C-OH and CH stretching vibration peaks, which means that the addition of zinc salt and iron salt increased the carbonization degree of carbon materials. -1 There is an obvious Fe-O stretching vibration peak at , which further proves that iron is successfully loaded on the carbon nanotubes. Figure 1 (e) It can be seen that the peaks on the carbon tubes due to the addition of zinc salts and iron salts are weak, indicating that in the absence of sodium hydroxide, zinc salts and iron salts are dissolved in the solvent and are difficult to load on the poplar fibers. After adding sodium hydroxide, Zn salts and Fe salts form precipitations and adhere to the poplar fibers. With high-temperature calcination, they are retained on the poplar porous carbon tubes.

[0084] 2. XRD analysis

[0085] The crystal structure of the carbon material is detected by X-ray diffraction to determine the orderliness of the pore structure of the carbon material.

[0086] X-ray diffraction of poplar fluff porous carbon tubes loaded with iron-zinc composites Figure 2 shown. Figure 2 (a) It can be seen that the diffraction peaks at 2θ = 44.8° and 2θ = 65.1° correspond to the (110) and (200) crystal planes of Fe, respectively, indicating that Fe 0 The existence of indicates that Fe is successfully loaded on the poplar fluff porous carbon. Figure 2 (b) It can be seen that the diffraction peaks at 2θ = 34.8°, 36.6°, 47.9°, 56.8°, and 63.1° correspond to the (002), (101), (102), (110), and (103) crystal planes of ZnO, respectively, indicating the presence of ZnO and indicating that Zn is successfully loaded on the poplar fluff porous carbon. Figure 2 Fe appears in (d, e) 0 In addition, the characteristic peaks of Fe2O3 appeared at 2θ=32.2° and 43.7°, indicating the presence of iron oxides and the excess Fe 3+The Fe2O3 crystal phase was formed in the calcined catalyst. At the same time, the characteristic peaks of ZnFe2O4 with normal spinel structure also existed in the catalyst. The diffraction peaks at 2θ=34.9° and 56.8° corresponded to ZnFe2O4, which indicated that Zn 2+ With some Fe 3+ After calcination, ZnFe2O4 crystals are formed. Under high temperature, part of Fe 3+ Reduced to Fe by C via carbothermal reduction 0 , part of Fe 3+ Fe2O3 and ZnFe2O4 were generated during high temperature calcination, so both Zn and Fe were successfully loaded on the poplar fluff porous carbon. Figure 2 (c) shows the main characteristic peak of Fe, while the characteristic peak of Zn is less. It is speculated that the amount of Fe and Zn salts added is small, and the Zn salt volatilizes as a porogen during the high-temperature calcination process. Figure 2 The characteristic peaks in (f) appear at 29.9, 35.3, and 62.2°, corresponding to the (220), (311), and (440) crystal planes of ZnFe2O4. This indicates that the loading amount of Fe and Zn salts on poplar fibers in the synthesis system without the addition of NaOH is small, and the carbon thermal reduction ability is weak, so they cannot be significantly reduced during calcination, thus showing obvious ZnFe2O4 peaks and weak Fe 0 Peak (2θ=44.8°).

[0087] 3. SEM analysis

[0088] Figure 3 (a, b, c) are SEM images of poplar fluff porous carbon, and (d, e, f) are SEM images of PC-Zn / Fe-2. As can be seen from the figure, the surface of the pretreated poplar fluff porous carbon is rough, with certain holes, and the tube wall of the poplar fluff porous carbon is also significantly thinner. Figure 3 (d, e, f) are poplar fluff-based flexible porous carbon tubes loaded with iron-zinc composite materials. The composite catalyst still maintains the tubular structure of poplar fluff fibers. In addition, nanoparticles are attached to the fiber tube wall and inside the tube. It can be seen that there are a small number of holes on the fiber tube wall, which is due to the evaporation of zinc salt at high temperature, which causes holes to be melted on the fiber tube wall. It can also be observed that the nanoparticles on the fiber surface are evenly embedded on the surface and wall of the carbon fiber, and the holes left by the ethanol-dissolved lignin on the tube wall are also loaded with nanoparticles, which greatly reduces the specific surface area of ​​the porous carbon material after loading iron-zinc nanoparticles, increases the contact area between the material and external substances, and is conducive to improving the adsorption performance of the carbon material.

[0089] 4. Mapping and EDS analysis

[0090] Depend on Figure 4It can be seen that C, O, Fe, and Zn elements are evenly distributed in the carbon nanotube structure. C mainly comes from carbon fibers, and Fe mainly comes from Fe 0 and Fe2O3, Zn comes from ZnO, in addition, Fe and Zn also come from ZnFe2O4 generated by the reaction. 0 , ZnO and ZnFe2O4 are evenly distributed on the carbon fiber tube, which is beneficial to improve the electron transmission capacity, enhance the photocatalytic ability, and improve the photoexcited charge carrier lifetime and electron transmission, thereby promoting the catalytic reaction. From the EDS spectrum, it can be seen that C atoms account for 33.58%, O atoms account for 60.21%, Fe atoms account for 5.41%, and Zn atoms account for 0.81%.

[0091] 5. Raman analysis

[0092] The samples were analyzed using a laser Raman tester, and the defect and graphitization degree of the carbon material were determined by the intensity ratio of the D peak and the G peak in the spectrum.

[0093] Depend on Figure 5 It can be seen that the above four materials have two obvious peaks, located at 1350cm -1 The D peak representing defective carbon in the graphite lattice and the G peak at 1580 cm-1 representing graphite carbon. D / I G It represents the ratio of the intensity of the D peak to the G peak. The larger the ratio, the higher the defective carbon content in the catalyst material. Conversely, the smaller the ratio, the higher the graphite carbon content in the catalyst material. Figure 5 (a) It can be seen that the I D / I G The value is 0.87, which has a higher degree of graphitization. When the poplar-based flexible porous carbon tubes are loaded with iron-zinc nanoparticles, the I D / I G The values ​​are all 0.97, which shows that the defective carbon content of PC-Zn and C-Fe is not much different, indicating that the introduction of Zn salt and Fe salt has a certain effect on the graphitization degree of carbon fiber. D / I G The value is 0.91, slightly lower than the I of PC-Zn and PC-Fe D / I G It is inferred that the synergistic effect of Zn salt and Fe salt is more conducive to the graphitization degree of carbon materials than that of single Zn salt and Fe salt. Zn salt and Fe salt can be used to induce more structural defects, which is conducive to the formation of more active sites and promotes the reaction.

[0094] 6. BET Analysis

[0095] Figure 6 N2 adsorption-desorption curves and pore size distribution diagrams of poplar fluff porous carbon loaded with different substances. Table 2 shows the specific surface area and pore volume of poplar fluff-based flexible porous carbon tube composite materials loaded with different substances. It can be seen that the specific surface area of ​​delignified poplar fluff porous carbon is about 517.764 m 2 / g, pore volume 0.455cm 3 / g, when only Fe salt was added to delignified poplar fibers, the specific surface area of ​​PC-Fe was about 36.631m 2 / g, which is greatly reduced. This may be because the nano-Fe porous growth on the carbon fiber wall and in the fiber pores blocked the original carbon pores, resulting in a decrease in specific surface area. When Zn salt was added to delignified poplar fluff fiber, the specific surface area of ​​PC-Zn was slightly reduced to about 401.875m 2 / g, which proves that the generation of zinc nanoparticles blocks the original pores on the fiber surface to a certain extent. At the same time, the introduction of zinc salt also plays its own role in pore formation, resulting in a less severe reduction in specific surface area than PC-Fe. Compared with PC-Fe, the specific surface area of ​​PC-Zn / Fe-2 is reduced, and the pore volume is reduced from 0.097cm 3 / g is reduced to 0.088cm 3 / g, which may be caused by the synergistic effect of iron and zinc salts, which proves that iron and zinc nanoparticles are successfully loaded on the carbon fiber tube wall. The average pore size of PC-Fe and PC-Zn / Fe-2 is significantly improved compared with PC-1 and PC-Zn. According to the comprehensive SEM images, it is speculated that Zn and Fe nanoparticles are accumulated on the fiber tube, forming new accumulation holes, which increases the average pore size of the composite material.

[0096] Table 2 Physical properties of different samples

[0097]

[0098] 7. Study on CO2 adsorption performance

[0099] Figure 7The adsorption performance of CO2 by different composite materials. As shown in the figure, the poplar fluff porous carbon has a good adsorption performance for CO2. At 273K and 101kPa, its CO2 adsorption capacity is 0.93mmol / g. When zinc salt is introduced, its adsorption capacity is greatly improved to 1.71mmol / g. This is mainly because PC-Zn is loaded with ZnO particles, which provide abundant CO2 adsorption sites through acid-base interaction and zinc-induced chelation. In addition, the porous space in PC-Zn composite fibers promotes the transport and capture of CO2 molecules. The adsorption capacity of PC-Fe and PC-Zn / Fe-2 for CO2 is very small. This may be because Zn and Fe in PC-Zn / Fe-2 block the pores of carbon fibers, resulting in a reduction in specific surface area and affecting the adsorption of CO2. In summary, PC-Zn composite fibers prepared with poplar fluff porous fibers have potential applications in gas adsorption.

[0100] In order to study the effect of different addition amounts of iron and zinc on the photo-Fenton performance of the catalyst, the obtained poplar floc-based flexible porous carbon tube-loaded iron-zinc composite material was used in the photo-Fenton dye degradation experiment, and the morphology of the catalyst was affected by changing the addition amount of Fe salt and Zn salt, pH, etc. Through the experiment to degrade different dyes, the catalytic performance of the catalyst on different dyes was explored, and the reusability of the catalyst was tested.

[0101] 1. Photo-Fenton degradation experiment of poplar fluff-based flexible porous carbon tubes loaded with iron-zinc composites

[0102] 50 mL of 300 mg / L RhB solution was measured and placed in a 100 mL double-layer jacket beaker, 0.05 mL of concentrated hydrochloric acid was added to adjust the pH of the solution to 2, and 20 mg of poplar-based flexible porous carbon tube-loaded iron-zinc composite material was added, and placed in a visible light multiphase photocatalytic reactor, the light source was a 500 W xenon lamp, and the temperature was maintained at 20 ° C using a water circulation system. The dark reaction lasted for 30 minutes to allow the system to reach adsorption-desorption equilibrium. After filtering 2 mL of the suspension with a 5 mL syringe, the absorbance was measured using a UV-visible spectrophotometer and recorded as the absorbance at time 0. After that, 0.1 mL of 30% H2O2 solution was added to the Rhodamine B (RhB) solution, and the xenon lamp was turned on at the same time to start the photo-Fenton reaction under the xenon lamp light source. The suspension was taken at 1min, 2min, 3min, 4min, 5min and 6min respectively, filtered, and its absorbance was measured. The absorbance was substituted into the standard curve equation of RhB to calculate the remaining RhB concentration and the degradation rate.

[0103] (1) Degradation of RhB

[0104] Figure 8The photo-Fenton degradation curve and kinetic curve of the poplar fluff-based flexible porous carbon tube-loaded iron-zinc composite material are shown in the present invention. In the present invention, the catalytic ability of the catalyst is demonstrated by degrading dye molecules simulating pollutants in water. Figure 8 The degradation efficiency of poplar fluff-based flexible porous carbon tubes loaded with iron-zinc composites for rhodamine B under visible light was demonstrated. PC-Zn is obtained by calcining poplar fluff with zinc salt, and has an adsorption effect on rhodamine B. PC-Fe is obtained by calcining poplar fluff with iron salt. PC-Fe has adsorption and degradation effects on rhodamine B, and the degradation effect is significant. PC-Zn / Fe-2 is obtained by simultaneously loading zinc salt and iron salt on poplar fluff and then calcining, and its degradation efficiency is higher than that of PC-Zn and PC-Fe. PC-Zn / Fe-4 only adds zinc salt and iron salt, and does not use NaOH to adjust the pH. The catalytic efficiency of the obtained catalyst is low. Combining the photo-Fenton degradation efficiency and kinetic curve, Figure 8 It can be seen that when only iron zinc salt is added to the synthesis system without NaOH (PC-Zn / Fe-4), the degradation rate is not high because the Fe and Zn loading on the poplar fluff porous carbon is small and has almost no catalytic effect. However, when NaOH is added, Fe and Zn are loaded on the poplar fluff porous carbon in large quantities and act together on the poplar fluff fibers, and the obtained sample has a higher degradation rate. Figure 8 It can also be seen that the degradation rate of PC-Zn / Fe-2 for 300mg / LRhB in 1min reached more than 99%, while the degradation rate of C-Fe / Zn prepared without delignified poplar fluff was only 51% in 1min, and it was degraded to 98% in 6min. This shows that the loaded iron-zinc composite material prepared by delignified poplar fluff-based flexible porous carbon tubes greatly improves its catalytic performance. The multi-porous structure of poplar fluff fibers allows zero-valent iron particles and carbon fibers to better combine to form a heterojunction. This structure helps to improve the electron transmission capacity, enhance the light absorption performance, and is beneficial to improve the photoexcited charge carrier lifetime, which is more conducive to the transmission of electrons and improves the catalytic performance of the material.

[0105] (2) Degradation of different dyes

[0106] In order to explore the degradation of different dye wastewater by PC-Zn / Fe-2 composite materials, methylene blue (MB) solution and MO solution were used for degradation experiments. The experimental conditions were the same as those for the degradation of rhodamine B (RhB). Fig. 9 It can be seen that PC-Zn / Fe-2 composite materials have significant catalytic degradation effects on methyl orange (MO), MB, and RhB pollutants. Among them, the degradation efficiency of RhB is the best, and the degradation rate reaches more than 99% in 1 minute. Compared with the degradation rates of MB and MO, the degradation rates are lower, but they are still relatively high in 1 minute. The adsorption of MB and MO is strong, which is speculated to be because MB and MO molecules are small and can be adsorbed by carbon fibers loaded with Fe and Zn. Fig. 9 It can be seen that the prepared PC-Zn / Fe-2 composite material has a high catalytic degradation effect on different types of organic dyes.

[0107] 2. 3D Fluorescence

[0108] Fig.10 The three-dimensional fluorescence spectrum of PC-Zn / Fe-2 degrading RhB. Fig.10 As shown in (a), the c1 peak at 500-580 / 640-700nm and the c2 peak at 200-320 / 560-660nm are the two characteristic fluorescence peaks of RhB. Fig.10 (b), the centers of peaks c1 and c2 did not move significantly, indicating that the adsorption effect of the catalyst on the degradation of rhodamine B was general. Fig.10 As shown in (c), as the photo-Fenton reaction proceeds, the reaction ends after 6 minutes, and both peaks c1 and c2 disappear, indicating that the RhB molecules have been completely decomposed into small inorganic salt molecules.

[0109] 3. Photo-Fenton cycle experiment of poplar fluff-based flexible porous carbon tubes loaded with iron-zinc composite materials

[0110] Measure 50 mL of 300 mg / L RhB solution and put it into a 100 mL double-layer jacket beaker, add 0.05 mL of concentrated hydrochloric acid to adjust the pH of the solution to 2, and add 20 mg of poplar-based flexible porous carbon tube-loaded iron-zinc composite material to start the photo-Fenton reaction. Do not take the supernatant in the middle. After the reaction is completed, pour the solution into a beaker, filter out the catalyst, repeatedly wash the catalyst with deionized water and anhydrous ethanol until the solution is colorless, and dry it. Start the next catalytic experiment. The catalytic experiment was repeated 4 times.

[0111] In actual industrial applications, the catalyst should not only have a high catalytic efficiency, but also have long-term stability and regeneration performance after multiple catalysis, so as to reduce a certain cost. The present invention uses the best catalyst PC-Zn / Fe-2 to conduct 4 cycles of catalytic degradation experiments. Fig.11 As shown, the catalytic efficiency of the four catalytic experiments was maintained above 99%, indicating that the prepared catalyst has good stability.

[0112] 4. Free radical capture experiment

[0113] 50 mL of 300 mg / L RhB solution was measured and placed in a 100 mL double-layer jacketed beaker. The pH of the solution was 2, the amount of H2O2 was 36 mM, the amount of PC-Zn / Fe-2 was 0.4 g / L, and free radical scavengers 0.5 mmol isopropanol (IPA), 0.5 mmol triethanolamine (TEA), and 0.05 mmol p-benzoquinone (BQ) were added to capture ·OH, h+ 、O2 - .

[0114] Through the above experiments, the photo-Fenton degradation mechanism can be obtained. Fig.12 The photo-Fenton performance of PC-Zn / Fe-2 with the addition of different free radical scavengers. In the experiment, isopropyl alcohol (IPA) was used to capture hydroxyl radicals (·OH), triethanolamine (TEOA) was used to capture photogenerated holes (h + ), p-benzoquinone (p-BQ) captures superoxide radicals (·O2 - ). Through free radical capture experiments, the reaction rate was significantly reduced after the addition of triethanolamine, indicating that the photogenerated holes h + As shown in the figure, when no free radical scavenger was added, the degradation rate of RhB by PC-Zn / Fe-2 within 1 minute was 99.31%, and the degradation rate after 6 minutes was 99.97%; after adding isopropanol, the degradation rate of RhB by PC-Zn / Fe-2 within 1 minute was 25.15%, and the degradation rate after 6 minutes was 84.15%. Compared with the case without free radical scavenger, the degradation effect of PC-Zn / Fe-2 on RhB was significantly weakened, indicating that hydroxyl radicals participated in the degradation reaction as active substances in the degradation reaction; after adding triethanolamine, the degradation rate of RhB by PC-Zn / Fe-2 within 1 minute was 25.15%, and the degradation rate after 6 minutes was 84.15%. The degradation rate was 5.86%, and the degradation rate was 13.93% after 6 minutes. The photo-Fenton reaction rate was significantly reduced. Compared with the case without free radical scavengers, the degradation effect of PC-Zn / Fe-2 on RhB was very significant, indicating that photogenerated holes participated in the degradation reaction as the main active substances in the degradation reaction; after adding p-benzoquinone, the degradation rate of RhB by PC-Zn / Fe-2 was 99.29% within 1 minute, and the degradation rate was 99.93% after 6 minutes, which was not much different from the degradation rate without free radical scavengers, indicating that superoxide radicals had a certain promoting effect on the reaction during the reaction, but were not the main active substances. The above results show that hydroxyl radicals and photogenerated holes participated in the reaction as the main active substances in the photo-Fenton degradation reaction of RhB by PC-Zn / Fe-2, and superoxide radicals had a certain coordination effect on the photo-Fenton degradation experiment, but were not the main active substances.

[0115] 5. Magnetic test of poplar fluff-based flexible porous carbon tubes loaded with iron-zinc composite materials

[0116] Depend on Fig.13 It can be seen that PC-Zn / Fe-2 is a black magnetic flocculent carbon fiber with strong magnetism, which can be adsorbed and fixed on the wall of the test tube by an external magnet. The excellent magnetic properties are helpful for the recovery of the catalyst after the reaction, which improves the convenience of catalyst use and its recyclability.

[0117] 6. Flexibility test of poplar fluff-based flexible porous carbon tubes loaded with iron-zinc composite materials

[0118] Depend on Fig.14 It can be seen that the flexibility test of the poplar fluff-based flexible porous carbon tube-loaded iron-zinc composite material was carried out, a certain amount of poplar fluff-based flexible porous carbon tube-loaded iron-zinc composite material was placed in a cylindrical container, and then a 50g weight basically the same as the inner diameter of the cylindrical container was placed in the cylindrical container, and the height of the poplar fluff-based flexible porous carbon tube-loaded iron-zinc composite material in the cylindrical container was measured. After removing the 50g weight, the poplar fluff-based flexible porous carbon tube-loaded iron-zinc composite material can still restore the deformation to a certain height. Therefore, the poplar fluff-based flexible porous carbon tube-loaded iron-zinc composite material has a certain flexibility, is not easy to break into powder, and is convenient for separation, recovery and recycling from water.

[0119] In summary, when poplar fluff fibers are modified jointly by iron salt, zinc salt and NaOH, when the addition amount of zinc and iron is 1mmol:2mmol and the pH is 9, the poplar fluff-based flexible porous carbon tube-loaded iron-zinc composite material calcined under a nitrogen atmosphere has the highest catalytic efficiency, and the degradation rate of 50ml 300mg / L RhB reaches more than 99% in 1min, and the degradation rate can reach 99% after 4 cycles; at the same time, the poplar fluff-based flexible porous carbon tube-loaded iron-zinc composite material has good catalytic performance for other dyes such as MB and MO, and 300mg / L of dye can be basically degraded in 2min.

[0120] Poplar fluff porous carbon has a good adsorption performance for CO2. At 273K and 101kPa, its CO2 adsorption capacity is 0.93mmol / g. After the introduction of zinc salt, its adsorption capacity is greatly improved to 1.71mmol / g, further indicating that poplar fluff porous carbon composites can be used in gas adsorption. The poplar fluff-based flexible porous carbon tube-loaded iron-zinc composite material has magnetism and flexibility, which facilitates the separation, recovery and recycling of the poplar fluff-based flexible porous carbon tube-loaded iron-zinc composite material from water.

[0121] In addition, the catkin-based flexible porous carbon tube-loaded iron-zinc composite material prepared in Example 4 has the same performance as the poplar-based flexible porous carbon tube-loaded iron-zinc composite material, both can be subjected to photo-Fenton catalytic degradation, and both can be used in the treatment of water pollution.

[0122] The above are only preferred embodiments of the present invention and the technical principles used. Those skilled in the art will understand that the present invention is not limited to the specific embodiments described herein, and that various obvious changes, readjustments and substitutions can be made by those skilled in the art without departing from the scope of protection of the present invention. Therefore, although the present invention is described in more detail through the above embodiments, the present invention is not limited to the above embodiments, and may include more other equivalent embodiments without departing from the concept of the present invention, and the scope of the present invention is determined by the scope of the appended claims.

Claims

1. A method for preparing a poplar / willow catkin-based flexible porous carbon tube-loaded iron-zinc composite material, characterized in that: The following steps are involved: The poplar / willow catkins are crushed, cleaned and dried to obtain pure poplar / willow catkins; the pure poplar / willow catkins are pretreated by an ethanol solvothermal method to obtain delignified poplar / willow catkins; Dissolving a trivalent iron salt and a divalent zinc salt in a solvent, stirring, and obtaining a mixed solution; Put the delignified poplar / willow catkins into the mixed solution and stir, and adjust the pH to alkaline to obtain a suspension; The suspension is stirred, filtered, the pH value is adjusted to be neutral, filtered by suction, and dried to obtain a poplar / willow catkin tube loaded with iron and zinc; The poplar / willow catkin tube loaded with iron and zinc is pre-oxidized and calcined to obtain a poplar / willow catkin-based flexible porous carbon tube loaded with iron and zinc composite material.

2. The method for preparing the poplar / willow catkin-based flexible porous carbon tube-loaded iron-zinc composite material according to claim 1, characterized in that: In the mixed solution, the concentration of the divalent zinc salt is 10mmol / L-30mmol / L, and the mass ratio of the trivalent iron salt to the divalent zinc salt is 1:2; in the suspension, the concentration of the delignified poplar / willow catkins is 8-12g / L.

3. The method for preparing the poplar / willow catkin-based flexible porous carbon tube-loaded iron-zinc composite material according to claim 1, characterized in that: The ferric iron salt includes one or more of ferric nitrate, ferric sulfate, and ferric acetylacetonate; the divalent zinc salt includes one or more of zinc nitrate, zinc chloride, and zinc acetate; and the solvent includes anhydrous ethanol; when the divalent zinc salt and the ferric iron salt are dissolved in the solvent, the stirring time is 10-60 minutes.

4. The method for preparing the poplar / willow catkin-based flexible porous carbon tube-loaded iron-zinc composite material according to claim 1, characterized in that: When the pure poplar / willow catkins are pretreated by the ethanol solvent thermal method, the specific process includes: adding pure poplar / willow catkins and ethanol into a reactor, sealing and heating for reaction, taking out and filtering to obtain pretreated poplar / willow catkins and lignin black liquor, washing the pretreated poplar / willow catkins with anhydrous ethanol, washing until the filtrate is clear, and obtaining delignified poplar / willow catkins.

5. The method for preparing the poplar / willow catkin-based flexible porous carbon tube-loaded iron-zinc composite material according to claim 4, characterized in that: The liquid-to-solid ratio of the ethanol to the pure poplar / willow catkins is (15-120):1, and the concentration of the ethanol is 40-80%. During the sealed heating reaction, the reaction temperature is 150-230° C., and the reaction time is 0.5-3.5 hours.

6. The method for preparing the poplar / willow catkin-based flexible porous carbon tube-loaded iron-zinc composite material according to claim 1, characterized in that: The pH is adjusted to alkaline, with a pH value of 9-10.

7. The method for preparing the poplar / willow catkin-based flexible porous carbon tube-loaded iron-zinc composite material according to claim 1, characterized in that: During the pre-oxidation process, the temperature is raised to 250-300°C at a rate of 0.5-2°C / min and kept warm for 30-90min; during the calcination process, the temperature is raised to 700-800°C at a rate of 3-6°C / min and kept warm for 30-90min, and an inert atmosphere is maintained during the calcination process.

8. A poplar / willow catkin-based flexible porous carbon tube-loaded iron-zinc composite material, characterized in that: Prepared by the preparation method according to any one of claims 1 to 7.

9. A photo-Fenton catalyst, characterized in that: It comprises the poplar / willow catkin-based flexible porous carbon tube-loaded iron-zinc composite material as described in claim 8.

10. The catalytic method of photo-Fenton catalyst according to claim 9, characterized in that: Photo-Fenton degradation was carried out under the conditions of different synthesis systems with different Fe-Zn doping amounts and alcohol or water phases.

Citation Information

Cited By

  • Lignin-based iron-carbon composite material as well as preparation method and application thereof

    CN121698458A